(untitled) (Proceedings of the International Conference on Sustainable Management for Peace and Harmony, 2025)
This case study analyzes Mother’s Recipe’s strategic approach to cultivating distinct market segments in India’s competitive ethnic food industry. Established in 2001, the company transformed from a traditional pickle manufacturer to India’s market leader across multiple food categories, operating in 45+ countries with over 150 product variants.The study examines how Mother’s Recipe differentiated itself through emotional branding centered on maternal love and traditional cooking values, using the "#TasteOfMothersLove" positioning to create authentic cultural connections. The company implemented sophisticated segmentation strategies including product diversification across traditional pickles, ready-to-cook products, and ready-to-eat meals, while deploying sub-brands (Rozana, Recipe, ELMAC) to address diverse price points and regional preferences.Key findings reveal successful market leadership through strategic combination of emotional positioning, geographic expansion with regional customization, omnichannel distribution, and continuous innovation. The company achieved strong financial performance with 15.12% net profit margin and significant revenue growth.The case provides valuable insights for marketing practitioners seeking differentiation in traditional industries, demonstrating that successful market cultivation requires authentic brand positioning supported by strategic segmentation and operational excellence. The study contributes to understanding emotional branding effectiveness and market segmentation strategies in emerging markets.